PREVALENCE OF MUTATIONS IN THE GENES OF M. TUBERCULOSIS CODING THE DRUG RESISTANCE TO ISONIAZID AND RIFAMPYCIN AMONG URBAN AND RURAL POPULATIONS OF SARATOV REGION - T. Yu. Salina; T. I. Morozova; A. N. Danilov (Туберкулез и болезни лёгких)
261 tuberculosis patients mainly su|ering from the pulmonary forms were enrolled into the comparative study of the pattern and prevalence of mutations in the genes of katG, inhA, ahpC and rpoB M. tuberculosis among urban and rural population. The testing was conducted with use of biological microchips and the set of reagents TB-Biochip, Russia. It has been found out that among tuberculosis patients constantly living in urban settings the multiple drug resistance is registered confidently more often compared to rural citizens – 38.6% against 23.2% respectively and the unfavorable pattern of mutations is detected in the genes of katG and rpoB, simultaneous multiple and concurrent mutations in 2-3 genes prevail. This requires development of additional measures of control over transmission of drug resistant strains of M. tuberculosis among urban population.